Restoring Soil and Water Resources and Mitigating Climate Change in India by Judicious Management of Agricultural and Urban Wastes - Lal, Rattan (Journal of the Indian Society of Soil Science, 2017)
Indiaâ€™s present population of 1.34 billion is increasing at the rate of 1.18% yr-1. Indiaâ€™s food grain production of 273.4 million tonnes (Mt) in 2017 has to be increased from lesser arable land area, lower fertilizer use and reduced consumption of water for supplementary irrigation. Furthermore, degraded soils, affecting land area of 114.2 million hectare (Mha), must be restored and risks of any new soil degradation minimized. In this context, the importance of recycling bio-wastes (e.g., agricultural, municipal and industrial) to restore soil organic carbon (SOC) concentration and stock and improve soil health cannot be over-emphasized. Crop residues, 510-836 Tg yr-1. are a major source of C, plant nutrients, biofuels and industrial raw materials. Rather than in-field burning and used as traditional fuel, composting and using as mulch can reduce risks of erosion and improve soil health. Similarly, dung production in India, also a rich source of C and nutrients, must be recycled as manure and used in bioreactors to produce methane. Wasted grains, fruits and vegetables must also be composted and used as a soil amendments. Judicious use of bio-wastes can re-carbonize the biosphere, restore degraded soils and improve soil health, produce biofuels and other value addition industrial byproducts, and improve the environment. Conservative estimates of additional soil C sequestration by judicious management of crop residues and animal dung are 24 Tg C yr-1 worth US 3.0 billion of revenue for farmers and land managers from payments for ecosystem services. There is a strong need of enhancing the awareness about proper disposal and use of bio-wastes through environmental education in primary and secondary schools, and communication by IT services. Recycling of bio-wastes is also critical to advancing the Sustainable Development Goals of the U.N. (Agenda 2030), promoting â€œ4 per Thousandâ€ program of COP21, and upholding the â€œSwatchh Bharatâ€ ideals. It is a win-win-win option.